STYLISTICS ANALYSES OF 'ONE ART', 'DO NOT GO GENTLE INTO THAT GOOD NIGHT', AND 'VILLANELLE OF SPRING BELLS' - Agustin, Ernawati; Bram, Barli (UIN Raden Mas Said Surakarta, 2023)
Stylistic elements play crucial roles in poetry writing, particularly for making poems sound more pleasing and meaningful. This paper, accordingly, aimed to find out the phonological, graphological, and grammatical features in villanelles,19-line poems with six stanzas, entitled One Art, Do Not Go Gentle into that Good Night, and Villanelle of Spring Bells. This study employed a descriptive-qualitative method with the data in the forms of 52 prepositional phrases. The findings indicate that, there are two main phonological features in the villanelles, namely consonance and assonance. Aside from that, each villanelle shows graphological features in the forms of different punctuation marks that reflect various meanings. There are also the uses of capital letters at the beginning of each stanza. Regarding the grammatical aspects, prepositional phrases have the highest frequency with the total of 52 occurrences in all the three villanelles. The use of these stylistic elements facilitates the readers to understand the messages of literary works. The readers could gain knowledge of the phonological, graphological, and grammatical features of villanelles by studying the stylistic elements in these three villanelles.